Recovering from earthquakes : response, reconstruction, and impact mitigation in India - Patel, Shirish B.; Revi, Aromar (New Delhi, India : Routledge, 2010)
Earthquakes come without warming, and often cause massive devastation, resulting not only in the loss of property but also of lives. Many of the survivors suffer from intense and lasting psychological trauma. This book covers the experience of various earthquakes in India, and what has been learnt in the process of managing the aftermath
1. Introduction:earthquake in India: reponse, recovery and impact mitigation -- 2. Disasters in India: policy overview of vulnerability, risks and human impact -- 3. The Uttarkashi earthquake: management of relief and rehabilition -- 4. Earthquake reconstruction in Maharashtra: impact on assets, income and equity -- 5. A decade of lessons from Marathwada: earthquake vulnerability, politics and participatory housing -- 6. Women take the lead: turning a crisis into an opportunity for development -- 7. Compounding disasters-first natural, then man-made: failed interventions we can learn from -- 8. Planning the reconstruction of Bhuj -- 9. Paarticipate rehabilition: a dilemma -- 10. Lessons from the gujarat experience: disaster mitigation and management -- 11. Disaster management in India: policy interventions and recent initiatives -- 12. Seismic retrofitting of existing non-engineered load-bearing structures -- 13. Medical management of earthquake disaster -- 14. Trauma after earthquakes: mitigating the psychosocial and mental effects -- 15. Catastrophe risk assessment and management: developing risk models for the insurance industry
Includes bibliographical references and index
Keywords: Earthquakes -- India; Emergency management -- India; Hazard mitigation -- India